The impacts of earthquake disaster on educational accessibility, affordability and continuity in Nepal - Nirmal Chongbang (SIMULACRA: JURNAL SOSIOLOGI, 2022)
Disasters can directly impact educational learning activities. Lower accessibility to socio-economic resources can directly impact into lives and livelihoods of a landless household. The study has explored how resourceless household struggle with their kid’s education accessibility, especially in earthquake disasters scenario in Gorkha Nepal. The research paper has explored existing education accessibility issues of pupils in the landless community. It has explained the major obstacle in educational accessibility impacted by the Gorkha earthquake of 2015 in Nepal. Descriptive and explanatory research methodology has been used. Primary information has been collected from a close-ended and open-ended questionnaire through local informants. Landless, education issues in disaster, and community-based initiatives related to publication information have been considered secondary sources of the study. Descriptive analysis has been used for qualitative data, and inferential data analysis has been for quantitative data. Education accessibility in the study area is hindered by a lack of local resources, additional earnings, insufficient savings, remoteness, weak physical structures, and a lack of social support. It is possible to enhance education accessibility for landless household pupils through community-based socioeconomic empowerment, collective engagement, and social protection provision.